2020
DOI: 10.1080/17538947.2020.1842524
|View full text |Cite
|
Sign up to set email alerts
|

A data fusion-based framework to integrate multi-source VGI in an authoritative land use database

Abstract: Updating an authoritative Land Use and Land Cover (LULC) database requires many resources. Volunteered geographic information (VGI) involves citizens in the collection of data about their spatial environment. There is a growing interest in using existing VGI to update authoritative databases. This paper presents a framework aimed at integrating multi-source VGI based on a data fusion technique, in order to update an authoritative land use database. Each VGI data source is considered to be an independent source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The UN SDG indicators use data from citizen science to monitor progress on the SDGs [35]. On the LULC side, Liu et al have shown how data collected through a web-based and mobile app called Paysages can be integrated with data fusion approaches into the official LULC map of the French National Mapping Agency [36]. Hence, there is considerable interest in using data from citizen science in official data sets.…”
Section: Discussionmentioning
confidence: 99%
“…The UN SDG indicators use data from citizen science to monitor progress on the SDGs [35]. On the LULC side, Liu et al have shown how data collected through a web-based and mobile app called Paysages can be integrated with data fusion approaches into the official LULC map of the French National Mapping Agency [36]. Hence, there is considerable interest in using data from citizen science in official data sets.…”
Section: Discussionmentioning
confidence: 99%
“…POIs generally refer to all geographical objects that can be abstracted as points and are mainly used to represent various service facilities in urban spaces. POI data cover spatial distribution and attribute the information of geographical objects, which are widely used in urban spatial structure and function analysis [ 27 , 28 , 29 ], vitality evaluation [ 30 , 31 ], and land cover verification [ 32 , 33 ]. POIs can be easily obtained by a special software development kit (SDK) provided by the Amap open platform ( , accessed on 1 January 2022), the acquisition methods of which include key-word search, peripheral search, ID search, etc.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…The Dempster-Shafer theory has been applied for fusing land cover information from different remote sensing imagery [55] and for urban change detection [56], but not to urban green space mapping in particular. In the context of volunteered geographic information, Comber et al [57] evaluated different methods including Dempster-Shafer theory for fusing classifications of multiple volunteers for land cover mapping and Liu et al [58] used Dempster-Shafer theory to update authoritative land use data with data collected from volunteers via in-situ and online mapping campaigns. Applications of Dempster-Shafer theory for fusing OSM and remote sensing data did not exists at the time of this writing.…”
Section: Related Workmentioning
confidence: 99%